Forecasts some of functional indicators nervous system for dribbling skills in young basketball players from Baghdad Governorate - Thaer Dawood Salman; Amjad Eabd Alhamid Almajid; Noura Amer Aliwi Al-Anazi; Saad Abbas Fadhil (Eximia, 2024)
The research study is important since it establishes predicted rates for various nervous system functional indicators.In terms of performing the skill of Dribbling in basketball for young players in Baghdad Governorate in order to reach scientific results that serve researchers, coaches, and players uniformly. The study’s goal is to create predictive equations for specific functional indicators of the nervous system in relation to the Dribbling skill performance of young basketball players in Baghdad Governorate. The researchers used a descriptive approach with a survey method on (8) youth basketball league clubs in Baghdad Governorate for the 2022-2023 sports season, totaling (96) players . Three tests were used to measure the nervous system, and one test was used to measure the basketball dribbling skill . After processing the data statistically, the researchers concluded that there was a contribution rate for the Romberg test (maintaining balance) As an indicator of the nervous system in terms of the performance of the dribble skill in basketball for young players by (3.5%), a prediction equation was developed for it. There is a contribution rate for the Yarotsk test (evaluation of the state of the vestibular system) as an indicator of the nervous system in relation to the performance of the basketball dribbling skill for young players by (5.6%), and a prediction equation was developed for it. The researchers recommended the need to direct coaches and specialists to pay attention to the results of this study in planning future programs to develop the true performance level of young basketball players. It is necessary to circulate the results of this study to sports and youth centers and sports clubs in order to rely on the tests used to judge the suitability of players to practice basketball.It is necessary to conduct similar studies on functional indicators of the nervous system and try to determine the percentage of their contribution in relation to other basketball skills that were not addressed in the current study and to establish predictive coefficients for them.It is necessary to conduct similar studies on functional indicators of the nervous system in relation to the performance of the basketball skill at other levels and for both genders.